2012
DOI: 10.1095/biolreprod.111.092262
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor Beta 1 Induces Tight Junction Disruptions and Loss of Transepithelial Resistance Across Porcine Vas Deferens Epithelial Cells1

Abstract: Epithelial cells lining the male excurrent duct contribute to male fertility by employing a number of physiological mechanisms that generate a luminal microenvironment conducive to spermatozoa maturation and storage. Among these mechanisms, male duct epithelia establish intercellular tight junctions that constitute a barrier to paracellular diffusion of water, solutes, large molecules, and cells. Mechanisms regulating the male duct epithelial barrier remain unidentified. Transforming growth factor beta (TGFB) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…Finally, the network involving cellular junction complex and integrity was examined. Interestingly, we found the increase in TGFBR1 that has been previously reported to induce tight junction dissociation . Such increase was consistent with the functional data demonstrating disruption of ZO‐1 expression and defective TER (Figure ).…”
Section: Discussionsupporting
confidence: 91%
“…Finally, the network involving cellular junction complex and integrity was examined. Interestingly, we found the increase in TGFBR1 that has been previously reported to induce tight junction dissociation . Such increase was consistent with the functional data demonstrating disruption of ZO‐1 expression and defective TER (Figure ).…”
Section: Discussionsupporting
confidence: 91%
“…The results confirm reports by Howe and colleagues [25] describing downregulation of CFTR by TGF-beta in T84 cells. Similar findings in the porcine vas deferens have been reported by Pierucci-Alves and colleagues [39] , and both of these studies identified p38 MAPK as a contributor to TGF-beta inhibition of CFTR. Our data also confirm recent reports in HAECs [26] , [37] , including downregulation of wtCFTR and F50del CFTR currents and expression produced by VX-809.…”
Section: Discussionsupporting
confidence: 87%
“…Even with certain MDCK cells (subtype MDCKII) apical activation by TGF-β has been reported [43]. Apical localization of TGF-β receptor I was also reported in porcine vas deferens epithelium [44]. In the kidney, Wang et al had provided evidence for apical expression of TGF-β receptors in a subset of rat cortical collecting duct cells, and showed in vitro reactivity of mouse proximal tubular cells and renal inner medullary cell lines (mIMCD-3 cells) upon apical stimulation with TGF-β [45].…”
Section: Discussionmentioning
confidence: 99%